Evaluating the Antiviral Activities of Human Cathelicidin LL-37 Peptide Against Rotavirus in Vitro - Zohreh Hosseini; Angila Ataei-Pirkooh; Mohammad Bagher Habibi Najafi; Masoud Yavarmanesh (The Journal of Qazvin University of Medical Sciences, 2019)
Background Rotavirus is the most prevalent cause of severe gastroenteritis, hospitalizations, and deaths among infants and young children, globally. No specific antiviral drug is available against rotavirus infection. Objective The current study aimed to assess the antiviral effect of human cathelicidin antimicrobial peptide LL-37 on rotavirus infection in vitro. Methods This study was conducted in the laboratory conditions of Iran University of Medical Sciences, in Tehran City, Iran. The neutral red assay was performed to assess the cytotoxicity of different concentrations of the peptide on the MA-104 cell line, and its antiviral activity was determined by TCID50 (50% tissue culture infective dose) assay. Findings According to the cytotoxicity results, viability maintained more than 90% up to the concentration of 50 μg/mL of LL-37 peptide. The antiviral assays results revealed that the concentration of 50 μg/mL LL-37 peptide could significantly reduce (3.36 log10 TCID50) the production of rotavirus progeny when administered before virus exposure (P= 0.0001). However, no inhibitory effect was detected after cell exposure to virus. Conclusion The obtained data suggested that LL-37 can be considered as a new antiviral agent for protecting infants and young children against gastroenteritis caused by rotaviruses. However, further in vivo investigations are required to confirm this finding.